KAJIAN BIAYA PEMUPUKAN TANAMAN BELUM MENGHASILKAN KELAPA SAWIT (Elaeis guineensis Jacq) DI AFDELING V KEBUN BATANG SERANGAN PT. PERKEBUNAN NUSANTARA II - Ingrid Ovie Yosephine; Sakiah Sakiah; Safar Hidayat (Universitas Asahan, 2019)
Fertilization is one of the key points in the cultivation of oil palm plantation and became one of the high-cost components. Needs of fertilizer per hectare oil palm plantation in approximately 24% of the total cost of production or approximately 40-60% of total maintenance. This research was carried out in the Afdeling V Batang Serangan Garden Perkebunan Nusantara II Company, Langkat Regency, North Sumatra Province. In March until August 2017. This research uses descriptive analysis method by knowing the total cost of fertilizing in immature plants (TBM) Palm oil. Based on the results of the analysis it can be concluded that the cost of fertilizing TBM palm oil cost amounted to Rp. 795.982.806,78/Ha at a cost of Rp. 6.150.860. The composition of the cost of fertilizing TBM I amounting to Rp. 1.138.726 (18%), TBM II of RP. 2.514.538 (41%), and TBM III Rp. 2.497.595 (41%) of the total overall costs. The composition of the cost of fertilizing TBM oil palm is the cost of purchasing the fertilizer 97%, a 1% transportation and fertilizer sowing of 2%.